2016
DOI: 10.1016/j.canlet.2015.10.024
|View full text |Cite
|
Sign up to set email alerts
|

The cyclic GMP/protein kinase G pathway as a therapeutic target in head and neck squamous cell carcinoma

Abstract: Head and neck squamous cell carcinoma (HNSCC) is an aggressive disease with high mortality. Treatments, which can result in significant morbidity, have not substantially changed in three decades. The second messenger cyclic GMP (cGMP), which targets protein kinase G (PKG), is generated by guanylate cyclases (GCs), and is rapidly hydrolyzed by phosphodiesterases (PDEs). Activation of the cGMP/PKG pathway is antineoplastic in several cancer types, but its impact on HNSCC has not been fully exploited. We found di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 41 publications
(37 reference statements)
2
49
0
Order By: Relevance
“…It has been reported that cGMP promoted tumorigenesis and anticancer effects. For example, the activated cGMP/PKG pathway induced multiple cancers (33,(35)(36)(37). Studies found specifically activated protein kinase G1 (PKG1) triggered MAPK signaling pathway to promote growth of melanoma (38).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that cGMP promoted tumorigenesis and anticancer effects. For example, the activated cGMP/PKG pathway induced multiple cancers (33,(35)(36)(37). Studies found specifically activated protein kinase G1 (PKG1) triggered MAPK signaling pathway to promote growth of melanoma (38).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that BAY reduced the viability of HNSCC cells primarily by inducing apoptosis, while only slightly reducing cell proliferation [22]. Here we examined whether YC-1 or BAY enhanced the apoptotic effects of cisplatin in HNSCC cells.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, PKG-Iα has been reported to have pro-tumorigenic effects [35, 36], while PKG-Iβ [37, 38] and PKG-II [13] had antineoplastic effects. Our previous studies have shown that all four HNSCC cell lines examined express PKGIβ and PKGII, but had no detectable levels of PKGIα transcripts [22]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cGMP can activate cGMP-dependent protein kinase (PKG) and PDE enzymes. It also causes ion fluxes and protein phosphorylation that can affect genes expression or other cellular responses [6,11,12] . Recently, the overexpression of PDE5 has been reported in several human carcinomas, including breast cancer, and suggested that PDE5 expression has positive correlation with tumor grade, lymph node involvement, and invasive potential, as well as decreasing survival rate in patients.…”
Section: Introductionmentioning
confidence: 99%